2007
DOI: 10.1128/aem.00828-07
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Mycobacterium avium in Drinking Water Biofilms as Affected by Water Flow Velocity, Availability of Phosphorus, and Temperature

Abstract: Mycobacterium avium is a potential pathogen occurring in drinking water systems. It is a slowly growing bacterium producing a thick cell wall containing mycolic acids, and it is known to resist chlorine better than many other microbes. Several studies have shown that pathogenic bacteria survive better in biofilms than in water. By using Propella biofilm reactors, we studied how factors generally influencing the growth of biofilms (flow rate, phosphorus concentration, and temperature) influence the survival of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 57 publications
(57 reference statements)
1
35
0
3
Order By: Relevance
“…However, since NTM species can grow under oligotrophic conditions (5,23), distribution of drinking water without a disinfection residual might increase the risk of NTM growth during distribution of the drinking water. On the other hand, studies have demonstrated that certain NTM species are especially resistant to monochloramine and that shifts from chlorine to monochloramine disinfection in drinking water treatment resulted in enhanced numbers of NTM in the drinking water distribution system (24)(25)(26).…”
mentioning
confidence: 99%
“…However, since NTM species can grow under oligotrophic conditions (5,23), distribution of drinking water without a disinfection residual might increase the risk of NTM growth during distribution of the drinking water. On the other hand, studies have demonstrated that certain NTM species are especially resistant to monochloramine and that shifts from chlorine to monochloramine disinfection in drinking water treatment resulted in enhanced numbers of NTM in the drinking water distribution system (24)(25)(26).…”
mentioning
confidence: 99%
“…Nesse estudo, foi observada que na parte da tarde as temperaturas encontravam-se naturalmente mais elevadas (30±1ºC) quando comparadas às temperaturas das amostras da mesma água coletada pela manhã (20±1ºC). Esses resultados foram semelhantes ao estudo realizado por Torvinen, et al (2007) que observaram elevadas contagens microbianas com o aumento da temperatura nos sistemas de distribuição de água potável.…”
Section: Coliformes Termotolerantesunclassified
“…Dentre os materiais utilizados o SS 316 e o policloreto de polivinila (PVC) foram termodinamicamente favoráveis para 6 tipos bacterianos, SS 304 para 18 tipos, e Copper, Polipropileno (PP) e Polietileno (PE) para 25 tipos de bactérias. A adesão é dependente da afinidade entre as propriedades físico-químicas da superfície bacteriana e dos materiais (Simões et al, 2007;Torvinen et al, 2007).…”
Section: Coliformes Termotolerantesunclassified
“…Toutefois, il est difficile d'étudier les biofilms formés dans le réseau de distribution en raison des contraintes industrielles occasionnées par le remplacement de sections de canalisation. Pour ce faire, des dispositifs expérimentaux ont été développés afin d'étudier la structure et la dynamique des biofilms formés sous l'action d'eau potable (BOE-HANSEN et al, 2003;DELAHAyE et al, 2006;KJELLERUP et al, 2004;MATHIEU et al, 2009;PARIS et al, 2007;PEREIRA et al, 2002;TORvINEN et al, 2007). Le principe de ces systèmes pilotes repose sur la colonisation de supports de même nature que les matériaux utilisés dans la construction des ouvrages de stockage et de distribution de l'eau potable.…”
Section: L'étude Des Biofilms Dans Le Système De Distibution D'eau Pounclassified